Influência da temperatura no consumo de água na região metropolitana de São Paulo - Torrente, Mauro (2014)
The Metropolitan Region of São Paulo (MRSP) is one of the locations, in Brazil, where water stress is at its most critical stage. According to the Falkenmark Indicator, used by the United Nations to measure water stress, the MRSP is classified facing an absolute scarcity of water . In this classification, the minimum required availability for a place not to be considered water scarced is 1,700 m³ per capita per year, and the MRSP has only 201 m³ per capita per year, less than 12 % of the minimum required volume. In March 2011, water resources managers of the MRSP manifested their concerns as to the risk of rationing the water supply, due to the occurrence of high temperatures. Based on this scenario, this survey, a case study in the MRSP for the period 2005-2012, aims to analyze, by literature review, internal corporate reports, periodic reports and technical documents, what is the influence of the atmospheric temperature on water consumption in the MRSP and, based in this verification, to propose strategies, to be used by water supply companies, to mitigate this influence and also to offer subsidies for public policies in water resources management. The research question that guided the survey is: What is the influence of the atmospheric temperature in the Metropolitan Region of São Paulo? As a result, it was observed that the temperature influences the water consumption, and that the water consumption of the MRSP is generally divided into two parts: the first part is the basic water consumption, which is independent of the effects of the air temperature, and the second is the seasonal consumption, directly influenced by the air temperature. Therefore, it is suggested the adoption of strategies which could start from a plan based on the verification of the short term and long term climate and weather trends, such as the influence of El Niño and La Niña, while incorporating practices that help reduce the demand for treated water.